NEURODEGENERATION AS AN EARLY SIGN OF DIABETIC RETINOPATHY - Dewi, Nadia Artha; Arfan, Muhammad; Rahmasari, Herisa; Putri, Mutiara Kristiani; Rosandi, Rulli; Kurniawan, Shahdevi Nandar (MNJ (Malang Neurology Journal), 2022)
Diabetic retinopathy is major cause of visual impairment and blindness in diabetic patients worldwide. The concept of diabetic retinopathy as vascular disease has established into not only microvascular complication but also neurodegeneration problems. Neurodegeneration plays an important role in pathogenesis of diabetic retinopathy. In fact, neuroretinal changes in diabetes can take place even before vasculopathy can be clinically detected.Â  This condition is marked by accelerated loss of neurons due to apoptosis, particularly in the inner retinal layer. The characteristic of neurodegeneration can be detected through retinal imaging and electrodiagnostics. This review is very crucial, because identifying the pathophysiology of diabetic neurodegeneration better, we may be able to provide interventions using the appropriate therapy. We may also be able to utilize these diagnostic toolsÂ  for early detections of diabetic retinopathy, thus preventing blindness due to diabetes.